1978
DOI: 10.1172/jci109027
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effect of glucose-insulin-potassium on myocardial performance during regional ischemia. Role of free fatty acid and osmolality.

Abstract: A B S T R A C T To evaluate the influence of glucose infusate administered with insulin and potassium on left ventricular function during 4 h of ischemia, as well as mechanism of action, four groups of intact anesthetized dogs were studied. Acute crease of plasma FFA in contrast to controls which manifested a significant rise. To examine the postulate that the decrease in FFA was important to therapeutic action, a third group was infused wvith Intralipid (Cutter Laboratories, Inc., Berkeley, Calif.) and hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Our findings are consistent with the majority of studies which have concluded that a benefit of GIK cannot be attributed exclusively to an osmotic effect (7,11,12,16), since osmolarity was balanced with sucrose in all of the solutions we used.…”
Section: Glucose)supporting
confidence: 92%
“…Our findings are consistent with the majority of studies which have concluded that a benefit of GIK cannot be attributed exclusively to an osmotic effect (7,11,12,16), since osmolarity was balanced with sucrose in all of the solutions we used.…”
Section: Glucose)supporting
confidence: 92%
“…1,21 In intact animals, high-dose insulin administration preserved regional LV function during 3 and post ischaemia. [3][4][5] One study attributed the effect solely to insulin. 1 In patients undergoing cardiac surgery, GIK infusion resulted in higher postoperative cardiac indices compared with patients receiving standard treatment.…”
Section: High-dose Insulin and Enhancement Of LV Functionmentioning
confidence: 99%
“…Most of these studies were performed in animal models [1][2][3][4][5] but also in patients undergoing cardiac surgery. [6][7][8][9][10] Dobutamine enhances overall myocardial performance and contraction, and high-dose insulin (HDI) infusion improves left ventricular systolic function in patients with left ventricular impairment due to ischaemic coronary disease.…”
mentioning
confidence: 99%
“…Increasing metabolism of glucose through glycolysis results in development of intracellular acidosis and accumulation of Ca +2 ions within the myocytes, which together lead to impairment of myocardial contractile function, myocyte injury and development of arrhythmias. Hence, inhibition of free fatty acid metabolism or increasing glucose delivery to the ischaemic myocyte has been shown to be beneficial both during ischaemia as well as during reperfusion [13][14][15][16][17]. It appears that in chronic LV dysfunction, the function of myocardium that shows contractile reserve can be improved by improving substrate supply [17].…”
Section: Perhexiline and Myocardial Metabolismmentioning
confidence: 99%